Employee Performance in Tourism Destinations: Readiness, Culture, and Leadership - Nur Rahmawati, Ummi; Andarini, Sonja (Jurnal Sains Sosio Humaniora, 2026)
The increasing implementation of digital systems in tourism operations requires employees to adapt quickly to technological changes while maintaining service quality. At Lembah Pandawa Tourism Destination, differences in employees’ digital readiness, adaptability to new work practices, and consistency of job performance indicate the need for effective human resource management strategies. This study aims to analyze the influence of digital readiness, adaptive work culture, and transformational leadership on employee performance. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 133 permanent and contract employees through a structured questionnaire. The findings indicate that digital readiness, adaptive work culture, and transformational leadership positively contribute to employee performance. These results emphasize the importance of enhancing digital competencies, encouraging adaptive work behavior, and strengthening transformational leadership to improve employee performance in tourism organizations. This study enriches the human resource management literature by providing empirical evidence from a developing tourism destination experiencing digital transformation.